2011
DOI: 10.1371/journal.pone.0023239
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Is Essential in the Upregulation of TRAF Proteins and NF-KappaB-Dependent Proinflammatory Gene Expression after Arterial Injury

Abstract: Despite extensive investigations, restenosis, which is characterized primarily by neointima formation, remains an unsolved clinical problem after vascular interventions. A recent study has shown that CD40 signaling through TNF receptor associated factor 6 (TRAF6) plays a key role in neointima formation after carotid artery injury; however, underlying mechanisms are not clearly elucidated. Because neointima formation may vary significantly depending on the type of injury, we first assessed the effect of CD40 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 48 publications
(81 reference statements)
4
31
0
Order By: Relevance
“…Involvement of NF-kB in the induction of Il23a mRNA expression under the CD40 signaling in BMDCs Because the transcription factor NF-kB is activated downstream of CD40 signaling, 21 we examined whether NF-kB was essential for the induction of Il23a mRNA expression in CD40-stimulated BMDCs and the synergistic action of EP4 signaling. Consistent with the previous report, the treatment with an anti-CD40 antibody augmented nuclear translocation of the NF-kB p65 subunit (Figure 2a), and increased phosphorylation of the NF-kB p65 subunit at serine 536 residue ( Figure 2b).…”
Section: Induction Of Il-23 In Bmdcs By Pge 2 -Ep4 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of NF-kB in the induction of Il23a mRNA expression under the CD40 signaling in BMDCs Because the transcription factor NF-kB is activated downstream of CD40 signaling, 21 we examined whether NF-kB was essential for the induction of Il23a mRNA expression in CD40-stimulated BMDCs and the synergistic action of EP4 signaling. Consistent with the previous report, the treatment with an anti-CD40 antibody augmented nuclear translocation of the NF-kB p65 subunit (Figure 2a), and increased phosphorylation of the NF-kB p65 subunit at serine 536 residue ( Figure 2b).…”
Section: Induction Of Il-23 In Bmdcs By Pge 2 -Ep4 Signalingmentioning
confidence: 99%
“…(f) Effect of NF-kB p100 depletion on Il23a mRNA expression in BMDCs stimulated with an anti-CD40 antibody with or without the EP4 agonist. BMDCs were treated with siRNA for p100 or scrambled siRNA for 48 h, and then stimulated with an anti-CD40 antibody (10 mg mL 21 ) and/or the EP4 agonist (ONO-AE1-329, 100 nM) for an additional 12 h. Total RNA from stimulated cells was prepared for quantitative RT-PCR analysis. n 5 3 in each group.…”
Section: Induction Of Il-23 In Bmdcs By Pge 2 -Ep4 Signalingmentioning
confidence: 99%
“…In stroke, TRAF3 is associated with neuronal death (11,13), although other associations with other neurological conditions such as spinal cord injury (SCI) (15) and multiple sclerosis (17) have also been observed. In cardiovascular disease, an altered expression of TRAF3 is related with cardiac hypertrophy (10), atherosclerosis (18,19) and arterial injury (20).…”
Section: Traf3 Expressionmentioning
confidence: 99%
“…Another study evaluated the role of CD40 and TRAF proteins in the underlying mechanism of restenosis (neointima formation) after artery injury in mice (20). The authors observed upregulation of CD40, TRAF proteins, including TRAF3, NF-κβ p65 and phospho-NF-κβ p65 in the injured carotid artery (20).…”
Section: Traf3 and Cardiovascular Diseasementioning
confidence: 99%
“…The current study shows that, NF-kB is strongly activated in the early stage of artery damage, and together with increasing expression of ICAM-1, MCP-1, TNF-a, IL-1b, IL-6 and so on. ICAM-1 and VCAM -1 strongly raise various inflammatory cytokines into the area, promoting the formation of vascular intima (Song et al, 2011). Studies on isolated endothelial cells show that ,isolated tumor endothelial cells (TEC) and normal endothelial cells (NEC), together, expressed CD31, CD105, VE-cadherin, vascular cellular adhesion molecule-1 (VCAM-1), ICAM-1, and E-selectin, and formed capillaries in basal membrane (Naschberger et al, 2011).…”
Section: Icam-1 and Hcc Metastasismentioning
confidence: 99%